Accuracy of the Surprise Question on an Inpatient Oncology Service: A Multidisciplinary Perspective. Issue 4 (August 2019) - Singh, Sarguni; Graham, Zachary; Rodriguez, Adrian; Lee, Darrell; Wenger, Barbara; Min, Sung-Joon; Fischer, Stacy
Abstract : The surprise question (SQ), "Would you be surprised if your patient died within a year?", has been studied in the cancer population as a prognostic prompt. Studies have almost exclusively directed the SQ to physicians, whereas perspectives of nurses remain underevaluated. We asked the SQ for patients admitted to an inpatient medical oncology service to medical oncology, palliative care, and hospital medicine teams and bedside nurses. We performed a 1-year retrospective chart review to identify how concordant various provider types were in their prognostic estimations and identified the missed opportunity rate (MOR) defined as the number of patients who died within a particular time frame but who the providers had predicted would be alive and may not have had a palliative approach. Oncologists had higher MORs for the 6-month and 1-year SQ when compared with hospital medicine providers. Bedside nurses were least concordant in their estimations of prognosis and had higher MORs for all time frames of the SQ. Missed opportunities might have significant implications for the end-of-life care for cancer patients, and continued research is needed to understand what influences provider prognostication and how this impacts palliative care utilization for patients with life-limiting disease.